ナンピョウヨウ サン ギョルイ ノ キセイチュウ ニ ツイテ - 影井, 昇; カゲイ, ノボル; 綿貫, 知彦; ワタヌキ, トモヒコ; KAGEI, Noboru; WATANUKI, Tomohiko (国立極地研究所, 1975)
P(論文) 1971年南極大陸昭和基地沿岸で採集したショウワギス,ウロコギス,ライギョダマシ,ボウズハゲギス,キバゴチの内部寄生虫について調査した結果,線虫類2種(Contracaecum sp. 幼虫,Ascarophis nototheniae),鉤頭虫1種(Echinorhynchus sp.),吸虫類2種(属種共に不明),条虫幼虫(plerocercoid)1種, Copepoda 1種を見出した.ボウズハゲギスからのAscarophis nototheniaeの報告は始めてであり(new host record), Echinorhynchusは吻における鉤の数と配列から新種と考えられた.吸虫類,条虫類, Copepodaは固定が悪かったこと並びに幼虫形態であることから属種の同定は出来なかった. In the survey on the parasites of the most common marine fishes from Antarctic Ocean, the authors observed on a new species; two species of Nematoda (larvae of Contracaecum sp. And Ascarophis nototheniae), two species of Trematoda (A and B), one species of Cestoda (plerocercoid), one species of Acanthocephala (Echinorhynchus sp.) and one species of Copepoda. Trematomus borchgrevinki is new host of A. nototheniae. departmental bulletin paper